2023
DOI: 10.1186/s12866-023-03065-8
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine Leukocidin (PVL) genes may not be a reliable marker for community-acquired MRSA in the Dakahlia Governorate, Egypt

Mohamed Shohayeb,
Tarek El-Banna,
Lamis E. Elsawy
et al.

Abstract: Background Methicillin-resistant Staphylococcus aureus is linked to both nosocomial and community infections. One of the key virulence factors of S. aureus is Panton-Valentine leukocidin (PVL). The PVL genes are mostly associated with community-acquired MRSA (CA-MRSA). This study evaluates the prevalence of PVL genes as a marker for CA-MRSA at tertiary hospitals in Mansoura, Dakahlia, Egypt. S. aureus was isolated from clinical specimens obtained from different departments of tertiary hospitals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…On the other hand, our research revealed that pvl gene was present in all S. aureus isolates. Therefore, our findings suggest that fish handlers could be the potential source of S. aureus contamination in the tested fish specimens since pvl gene was originally and commonly associated with community-acquired MRSA (CA-MRSA) isolates and was infrequently identified in hospital-acquired MRSA (HA-MRSA) isolates (Shohayeb et al, 2023). Moreover, only one isolate contained tst gene which encodes TSST-1 protein, and this protein is a crucial virulence determinant of S. aureus leading to a multiple organ dysfunction (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, our research revealed that pvl gene was present in all S. aureus isolates. Therefore, our findings suggest that fish handlers could be the potential source of S. aureus contamination in the tested fish specimens since pvl gene was originally and commonly associated with community-acquired MRSA (CA-MRSA) isolates and was infrequently identified in hospital-acquired MRSA (HA-MRSA) isolates (Shohayeb et al, 2023). Moreover, only one isolate contained tst gene which encodes TSST-1 protein, and this protein is a crucial virulence determinant of S. aureus leading to a multiple organ dysfunction (Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 92%
“…According to the comparison of antibiotic resistance patterns among MRSA isolates from teaching hospitals [26,27].…”
Section: Discussionmentioning
confidence: 99%